Torsional Design of Round HSS Members— A Critical Review - Dowswell, Bo (Engineering Journal, 2024)
Shear yielding is the controlling limit state for most round HSS members subjected to torsion; however, buckling is a limit state that can reduce the torsional strength of members with high diameter-to-wall thickness (D/t) ratios. The purposes of this paper are to summarize the available research on the torsional performance of round HSS members and evaluate the applicable provisions in the AISC Specification. A historical review of the available research revealed 125 experimental tests from seven projects, leading to evolving design methods over the last century. An evaluation of the AISC Specification provisions indicated an appropriate reliability level for the yielding limit state; however, the target reliability for buckling is met only for long specimens. A new equation is proposed to predict the buckling strength of intermediate-length members.